Rzeźbiarz i filozof. Constantin Brâncuşi w interpretacjach Constantina Noiki - Zawadzki, Andrzej (Przestrzenie Teorii, 2019)
The article Sculptor and philosopher deals with the Romanian thinker Constantin Noica’s interpretations of Constantin Brâncuşi’s work. These interpretations are presented with regard to Noica’s philosophical concepts, in particular his reflections on Romanian culture and the sense of being manifested within it. Of fundamental importance in his interpretations is the category of becoming within being – the most important idea developed by Noica and which he applied in many fields of philosophy.